Clement Greenberg’s “Modern and Postmodern”: the Apology of Modernism in the Postmodern Era - Chunikhin, Kirill A. (Actual Problems of Theory and History of Art, 2013)
The article explores Clement Greenberg’s unrenowned essay “Modern and Postmodern” (1980) in which the famous art-critic attacks his own definition of “modernism as self-criticism” stated in his 1961 article “Modernist Painting”.
Keywords: Clement Greenberg; modernism; history of American art-criticism